Is Surgical Resection Justified for Advanced Intrahepatic Cholangiocarcinoma? - Yoh, Tomoaki (Liver Cancer, 2016)
BACKGROUNDS: Prognosis for patients with advanced intrahepatic cholangiocarcinoma (ICC) with intrahepatic metastasis (IM), vascular invasion (VI), or regional lymph node metastasis (LM) remains poor. The aim of this study was to clarify the indications for surgical resection for advanced ICC. METHODS: We retrospectively divided 213 ICC patients treated at Kyoto University Hospital between 1993 and 2013 into a resection (n=164) group and a non-resection (n=49) group. Overall survival was assessed after stratification for the presence of IM, VI, or LM. RESULTS: Overall median survival times (MSTs) for the resection and non-resection groups were 26.0 and 7.1 months, respectively (p<0.001). After stratification, MSTs in the resection and non-resection groups, respectively, were 18.7 vs. 7.0 months for patients with IM (p<0.001), 23.4 vs. 5.7 months for those with VI (p<0.001), and 12.8 vs. 5.5 months for those with LM (p<0.001). CONCLUSION: When macroscopic curative resection is possible, surgical resection can be justified for some advanced ICC patients with IM, VI, or LM.